Social work curricular design and the international standards for the profession: Alignment and misalignment in Portugal - Justino, E.; Dias, D. (EDULEARN23 Proceedings, 2023)
One of the main features of Social Work as a field of science is that training and practice have always been articulated, as one inevitably impacts on the other. Thus, the Bologna guidelines have not implied the same deep adjustments as in other disciplines, since social work has always been closely aligned with prevailing practices. Its definition as a scientific field implies that social work is both a practice-based profession and an academic discipline. The principles of human rights, social justice, and equity are central to Social Work, and therefore to higher education. However, the curriculum design, over time and in different geographies, shapes itself according to the historical and/or social contexts in which it develops. This paper aims to compare the learning outcomes for Social Work degree programs in Portugal with the Global Standards of Education and Training, established by the International Association of Schools of Social Work (IASSW) and the International Federation of Social Workers (IFSW). In other words, this study intends to validate if, educational institutions that teach social work degrees in Portugal align their curricular design with the international standards for the profession. Adopting a qualitative approach, the learning outcomes of all social work degrees in portugal were semantically analyzed using content analysis underpinned by the grounded theory paradigm. Thus, the frequency and different classes of the learning outcomes of all degree programs were explored. With the results of the semantic analysis of the learning outcomes it was proceeded, in a second step, to compare them with the standarts established by the International Association of Schools of Social Work (IASSW) and the International Federation of Social Workers (IFSW). The results point to some misalignment between the learning outcomes of Portuguese higher education degrees in social work and the international standards and guiding principles in this scientific area. In this regard, Portuguese higher education institutions should reinforce their concern with some dimensions of social workers profile, i.e. ethical issues, problem-solving and communication skills.